2019
DOI: 10.1186/s12891-019-2997-y
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cervical Discectomy and Fusion combined with thyroid gland surgery, a tailored case and literature review

Abstract: BackgroundNowadays, Anterior Cervical Discectomy and Fusion (ACDF) is considered a routine procedure. However, unexpected difficulties do occasionally arise, especially when anterior neck pathologies or anatomical variations are encountered. In such cases, proactive thinking will allow surgeons to tailor appropriately their approach and eliminate surgical risks.Case presentationWe present the case of a 50-year-old male patient suffering from left upper limb radiculopathy that underwent a C7-T1 ACDF combined wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In anterior cervical surgery, vigorous mobilization of the thyroid gland, especially the development of a goiter, may damage the recurrent laryngeal nerve (9). Previous studies also reported anterior cervical discectomy and fusion combined with thyroid gland surgery when a goiter is encountered during cervical surgery (9,10). However, the prevalence of thyroid abnormalities in patients with cervical spondylosis requiring surgery is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In anterior cervical surgery, vigorous mobilization of the thyroid gland, especially the development of a goiter, may damage the recurrent laryngeal nerve (9). Previous studies also reported anterior cervical discectomy and fusion combined with thyroid gland surgery when a goiter is encountered during cervical surgery (9,10). However, the prevalence of thyroid abnormalities in patients with cervical spondylosis requiring surgery is unclear.…”
Section: Introductionmentioning
confidence: 99%